2016
DOI: 10.1159/000447252
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intestinal Permeability and Decreased Barrier Function: Does It Really Influence the Risk of Inflammation?

Abstract: Background: Increased intestinal permeability due to barrier dysfunction is supposed to cause microbial translocation which may induce low-grade inflammation in various diseases. However, this series of events has not been comprehensively evaluated yet. Summary: Intestinal epithelial barrier dysfunction and increased permeability have been described in patients with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), alcoholic liver disease, nonalcoholic steatohepatitis (NASH), liver cirrhosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(220 citation statements)
references
References 110 publications
(137 reference statements)
3
192
1
11
Order By: Relevance
“…Dietary assessment studies have shown that PACs, especially procyanidins, are among the most abundant polyphenols in the human diet [6], as they are present in a variety of botanical sources and plant food products such as tea, fruits, nuts, cacao products, legumes, and cereal grains [1,2]. However, PAC intake varies widely between geographical regions and cultures and is greatly dependent on eating habits, lifestyle behaviors, and socioeconomic status [78].…”
Section: Pacs: Chemical Structure Occurrence and Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Dietary assessment studies have shown that PACs, especially procyanidins, are among the most abundant polyphenols in the human diet [6], as they are present in a variety of botanical sources and plant food products such as tea, fruits, nuts, cacao products, legumes, and cereal grains [1,2]. However, PAC intake varies widely between geographical regions and cultures and is greatly dependent on eating habits, lifestyle behaviors, and socioeconomic status [78].…”
Section: Pacs: Chemical Structure Occurrence and Intakementioning
confidence: 99%
“…When there are disturbances in the barrier function and mucosal immune homeostasis, the influx of intestine luminal content triggers an exaggerated mucosal immune response [1]. Ultimately, chronic exposition to these detrimental environmental stimuli may lead to the development of local and systemic inflammatory conditions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In IBS patients, GI dysbiosis has been associated with a visceral increased perception of pain and enhanced mucosal permeability that is provoked by the defective mucosal epithelial barrier, interfering with gut immune homeostasis and subsequently promoting gut inflammation and enhancing cellular and mucosal immune activation [28,29]. Moreover, it has also been associated with changing gut motility, low-grade chronic inflammation, alterations of the enteric nervous system, and vagal afferents neurons as well as brain functions [30][31][32].…”
Section: The Microbiome In Ibsmentioning
confidence: 99%
“…Therefore, when these epithelial barriers break down, external toxins, allergens, and pollutants penetrate into the body, thereby inducing and accelerating inflammation for defense against them 1 2 . In addition, breakdown of epithelial barrier result in increased epithelial permeability, which allows internal leakage such as diarrhea and jaundice 3 …”
Section: Introductionmentioning
confidence: 99%